Malay descendant communities in China = Masyarakat Melayu di negara China - Liu, Yusuf Baojun, 1963- (Kuala Lumpur : Saba Islamic Media, 2013)
Apart from more than three hundred million Malays living in the vast Malay Archipelago, the early marine navigation and colonisation factors also saw the Malay diaspora societies being distributed around the world, such as Cape Town, South Africa; Australia, Sri Lanka, China and other countries thereby reflecting their communication and emigration history.
Ever since Cheng Ho's visitation to Southeast Asia during the Ming Dynasty, the relationship between the Malay community and China has become even closer. In the land of China there were three Malay Kings who were buried here. Besides, the communities of the Malay descendants can also be found in Hainan Island, Nanjing, Dezhou, Taiwan and other places. The Malay Descendants Communities in China is a pioneering illustrated book of relevant documents and photographs, which features the history and current situation of the Malay descendants in a synthesized approach.
Text in English, Chinese and Malay.
Keywords: Islam -- China -- History; Muslims -- China -- History; Muslims -- China -- Social life and customs; Malays -- China -- History